Ecolinguistics, Speciesism, Emotion and Transposition in Multimodal Texts : Official Narratives in YouTube - Forte, Diego L. (Universitas Andalas, 2025)
Narratives play a central role in our daily lives. They organize to the possibilities of our culturally bounded material world by teaching the roles, processes and emotional parameters of our particular community. Through social life, we acquire a framework of references to interpret our experiences and negotiate meanings (Bruner & Haste, 1990). But narratives do not stand still in a material support. Since their oral origins, they have move to stone, codex, books, digital formats and countless material ways to transmit them. This is to say they transpose from one media to other and from one genre to other, adapting itself to the possibilities each support/genre offers. Modern media and genres involve nowadays multimodal texts, which means that there is also a movement from one mode to another (Lim and Tan-Chia, 2023: 90). By definition legislative and legal genres constitute a part of the legal framework established by government officials to address complex societal issues (Dimok, 2012: 338). As discourse, they involve a discursive and a social practice but, unlike many other genres, they provide material resources to protect the representations they include. Nevertheless, in their spirit of enforcing behaviours, legislative and legal genres present limitations. The same feature that grants them a high hierarchy also constrains their reach: normative language does not sell; it is not suitable for a mass audience. So, these meanings must be re-written into a broader construction for non-expert auditoriums. In this work we use ecolinguistics as main theoretical framework to investigate the construction and transposition of emotional meanings in food legislation regarding the 2019 Bird flu outbreak in Argentina. We adopt the systemic-functional tools proposed by Kress and van Leeuwen (2005) for image analysis; Ekman & Friesen (1978, 1986) and Ekman (2003) for facial expressions of emotion and Forte (2023a) for music analysis.